1991
DOI: 10.1159/000110269
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis in Galion, Ohio: Prevalence and Results of a Case-Control Study

Abstract: An investigation of the occurence of multiple sclerosis (MS) was undertaken in the City of Galion, Ohio, USA, because of a report of an increased number of cases. As of June 1,1987, there were 18 living cases of MS in Galion and Polk Township, for a prevalence rate of 112 cases per 100,000 population. The expected rate is approximately 65–170 cases per 100,000. In a case-control study, residents of Galion or Polk Township who had MS were compared to residents who did not have MS. The controls were matched to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
0
30
2
Order By: Relevance
“…In examining the epidemiologic data on sex hormones and MS, we focused on 4 hormonal risk factors: (1) age at menarche: we found 5 case-control studies, 4 of which we graded as 'c' [36,[70][71][72] and 1 of which we graded as 'b/c' [73]; (2) pregnancy: we found 3 case-control studies of which 1 was graded as 'b' [44] and 2 as 'c' [70,74]; (3) parity: we found 3 cohort studies, 2 of which we graded as 'b' [75,76] and the other as 'b/c' [77]. Two case-control studies were also identified, both of which we graded as 'c' [36,70], and (4) oral contraceptives: we found 3 cohort studies, 2 of which we graded as 'b' [75,76] and the other as 'b/c' [77].…”
Section: Sex Hormonesmentioning
confidence: 99%
“…In examining the epidemiologic data on sex hormones and MS, we focused on 4 hormonal risk factors: (1) age at menarche: we found 5 case-control studies, 4 of which we graded as 'c' [36,[70][71][72] and 1 of which we graded as 'b/c' [73]; (2) pregnancy: we found 3 case-control studies of which 1 was graded as 'b' [44] and 2 as 'c' [70,74]; (3) parity: we found 3 cohort studies, 2 of which we graded as 'b' [75,76] and the other as 'b/c' [77]. Two case-control studies were also identified, both of which we graded as 'c' [36,70], and (4) oral contraceptives: we found 3 cohort studies, 2 of which we graded as 'b' [75,76] and the other as 'b/c' [77].…”
Section: Sex Hormonesmentioning
confidence: 99%
“…Second, relevant exposures of interest are unmeasured, particularly historical exposures that are needed to help determine the latency of disease. Cluster investigations of MS in the USA have typically been conducted in areas where there is local concern regarding exposure from a hazardous waste site [7][8][9]. Unfortunately, past exposure information at the individual or pertinent geographic area level is generally not available so studies rely on self-reported exposure information.…”
Section: Inability Of Cluster Studies To Address Community Concernsmentioning
confidence: 99%
“…Third, the small number of cases in such (clusters) often limits the ability to differentiate between an excess of etiologic interest and a chance occurrence. MS cluster investigations have been conducted with less than 10 individuals [23,24] although most have less than 40 individuals [7][8][9].…”
Section: Inability Of Cluster Studies To Address Community Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A case-control study by Hopkins et al investigated complete occupational histories, but there was little correlation between MS and "exposure to various chemicals, radiation, or potentially toxic gases". 10 In a prospective cohort study consisting of 124,766 "solvent-exposed" Danish men and 87,501 "solvent-unexposed" Danish men, both groups were followed over a period of 20 years. After 20 years of follow-up, the number of MS cases among men presumed to be exposed to organic solvents was similar to the number of cases expected on the basis of the rates in all Danish men.…”
Section: Multiple Sclerosismentioning
confidence: 99%